2012
DOI: 10.5336/medsci.2011-25866
|View full text |Cite
|
Sign up to set email alerts
|

Serum Total Antioxidant Status, Lipid Profile, Malondialdehyde and Erythrocyte Superoxide Dismutase Levels in Hashimoto Thyroiditis Patients Treated with Levothyroxine

Abstract: A AB BS ST TR RA AC CT T O Ob bj je ec ct ti iv ve e: : To compare the serum level of total antioxidant status (TAS), malondialdehyde (MDA) and erythrocyte superoxide dismutase (SOD) levels in Hashimoto thyroiditis patients treated with levothyroxine and healthy control subjects and to assess possible correlations of these parameters with biochemical parameters such as glucose and lipid profile. M Ma at te er ri ia al l a an nd d M Me et th ho od ds s: : SOD, TAS, MDA, fasting glucose, lipid profile, thyroid h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In the current study, NP-SH was significantly reduced by 12 months of LRT, but no significant changes were observed in T-SH, δ-ALA-D or TBARS. Some studies have shown reduction of oxidative stress after LRT, [ 18 , 23 , 29 ], while other studies have reported no modification [ 19 , 20 ]. Marfella et al [ 26 ] detected elevated OS biomarkers in atherosclerotic plaques of SCH subjects compared to control plaques, and higher levels of OS in plaques of untreated SCH patients in comparison with plaques of treated SCH patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, NP-SH was significantly reduced by 12 months of LRT, but no significant changes were observed in T-SH, δ-ALA-D or TBARS. Some studies have shown reduction of oxidative stress after LRT, [ 18 , 23 , 29 ], while other studies have reported no modification [ 19 , 20 ]. Marfella et al [ 26 ] detected elevated OS biomarkers in atherosclerotic plaques of SCH subjects compared to control plaques, and higher levels of OS in plaques of untreated SCH patients in comparison with plaques of treated SCH patients.…”
Section: Discussionmentioning
confidence: 99%
“…For the five thyroid function parameters, there were strong positive correlations among TSH, T4, T3, FT3, and FT4 (r=0.4-0.8, P<0.01), which could be explained by T3 being the more metabolically active hormone produced by T4. T4 is deiodinated by three deiodinase enzymes and produces the more active T3 (42). Nevertheless, no correlations were observed between concentrations of total PBDEs to age or BMI (P>0.05).…”
Section: Spearman's Correlation Between Total Pbde Concentration and Thyroid Function Parametersmentioning
confidence: 96%